METHODS OF RECOGNITION AND RECOMMENDATIONS FOR LOCALIZATION OF ELECTROMAGNETIC INTERFERENCE IN THE SYSTEM "SMART HOUSE" (Modern information system and technologies, 2018)
Given the large number of problems and factors associated with the electromagnetic environment, this article discusses the ways of recognizing electromagnetic interference in the smart house system. The choice of electronic components, namely, the R&S NRP-Z and NRPxS/SN power sensors, for identification of electromagnetic interference. The ways of integrating the R&S NRP-Z and NRPxS/SN power sensor into the «smart home» system are demonstrated and recommendations for localization of electromagnetic interference sources from undesirable effects are developed. Additional possibilities of the «smart house» system are revealed.